Barriers and facilitators of positive psychological intervention online in the COVID-19 pandemic - Bedinoto Durgante, Helen (2025)
This study evaluated the online implementation of a positive psychological intervention for retirees during the COVID-19 pandemic in Brazil. A mixed longitudinal design with pre-post-intervention and implementation process evaluation was used. Thirty convenience retirees aged between 52-87 years participated (M=65.13; SD=9.22). The instruments were: a sociodemographic questionnaire, visual analog scale, program and sessions’ evaluation form, and moderator’s field diary. Participants’ mood improved after the themes: values and self-care, optimism, empathy, meaning of life, and work. The best evaluated relaxation technique involved elements of Mindfulness and the most used contents were Gratitude and Empathy. There were difficulties in using technologies (access to the online room, connection instability, noise from the environment) and the non-private domestic context for the sessions. In one group, there was a reduction in time and an increase in the number of sessions to avoid fatigue. It was suggested an increase in the number of sessions and participants, groups outside working hours, or during household chores. We expect to contribute to the production of knowledge on online interventions for health promotion, considering the pandemic moment of the country.